Performance of Ultra-High Performance Fiber Reinforced Concrete Columns Under Blast Loading - Dagenais, Frederic (Université d'Ottawa / University of Ottawa, 2016)
Recent attacks and accidental explosions have demonstrated the necessity of ensuring the blast resistance of critical buildings and infrastructure in Canada such as federal and provincial offices, military buildings and embassies. Of particular importance is the blast resistance of ground-story columns in buildings which must be properly detailed to provide the necessary strength and ductility to prevent progressive collapse. There exists a need to explore the use of innovative materials that can simultaneously improve the performance of such columns, while also allowing for a relaxation of required detailing to ease construction. Advancements in concrete material science have led to the development of ultra-high performance fiber reinforced concretes (UHPFRC) which show superior mechanical properties when compared to conventional concrete, such as increased compressive strength, tensile resistance and toughness. These enhanced properties make UHPFRC an attractive material for use in the blast design of reinforced concrete columns. This thesis presents the results of a research program examining the performance of UHPFRC columns under simulated blast loads. As part of the experimental program twelve half-scale UHPFRC specimens, six built with regular grade steel reinforcement and six built with steel high-strength steel reinforcement, are tested under blast loading using the University of Ottawa shock tube. The specimens were designed according to CSA A23.3 standard requirements for both seismic and non-seismic regions, using various fibre types, fibre amounts and longitudinal reinforcement ratios, allowing for an investigation of various design parameters on blast behaviour. The results demonstrate that the use of UHPFRC improves the blast performance of columns by reducing displacements, increasing resistance and enhancing damage tolerance. The results also indicate that fiber content, fiber properties, seismic detailing, longitudinal reinforcement ratio and longitudinal reinforcement strength are factors which can affect the behaviour and failure mode of UHPFRC columns. As part of the analytical study the response of the UHPFRC columns is predicted using dynamic inelastic analysis. The dynamic responses of the columns are predicted by generating dynamic load-deformation resistance functions for UHPFRC and conducting single-degree-of-freedom (SDOF) analysis using software RC-Blast.